Mass Transfer Characteristics in a Rotor‐Stator Reactor. Issue 6 (27th April 2017) - Zhao, Zemeng; Zhang, Xiu; Li, Guangjun; Chu, Guangwen; Sun, Baochang; Zou, Haikui; Arowo, Moses; Shao, Lei
Abstract: Mass transfer characteristics in a rotor‐stator reactor in terms of the overall volumetric mass‐transfer coefficient ( Kx a ) using the N2 ‐H2 O‐O2 system were investigated. The effects of various operating parameters including rotation speed, liquid volumetric flow rate, and gas volumetric flow rate on Kx a were systematically examined, and a gas‐liquid mass transfer model was established to predict Kx a. Results reveal that Kx a increased with higher rotation speed, liquid volumetric flow rate, and gas volumetric flow rate. The results also confirm that the predicted values of Kx a were in agreement with the experimental values with deviation within 15 %. The results contribute to a better understanding of mass transfer characteristics in rotor‐stator reactors. Abstract : Rotor‐stator reactors are promising multiphase mass transfer contactors for process intensification in the chemical industry. The N2 ‐H2 O‐O2 system was employed to analyze their mass transfer characteristics. The overall volumetric mass transfer coefficient Kx a was investigated as a function of various operating conditions. A gas‐liquid mass transfer model to predict Kx a was established.